Method for synthesizing Co2Mn0. 1Ru0. 9O4 nanostructure and application of Co2Mn0. 1Ru0. 9O4 nanostructure

By synthesizing the CO2MN0.1RU0.9O4 nanometer structure, optimizing the process conditions and element ratio, the problem of the alternative of IRO2 anode materials in PEM hydrolysis, realizing the reaction and stability of efficient oxygen analysis, reducing costs.

CN119370918APending Publication Date: 2025-01-28YANGTZE DELTA REGION INST OF UNIV OF ELECTRONICS SCI & TECH OF CHINE (HUZHOU)
View PDF 0 Cites 0 Cited by

Patent Information

Application Number
CN202411511327.5
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Filing Date
2024-10-28
Publication Date
2025-01-28

AI Technical Summary

Technical Problem

In the prior art, IrO2 in PEM water electrolysis has problems of limited supply and high cost as anode material, and is prone to corrosion in an acidic environment, making it difficult to find alternative catalysts to improve the efficiency of oxygen precipitation reaction (OER).

Method used

By synthesizing the CO2MN0.1RU0.9O4 nano structure, ethanol solvents and air annealing are used to optimize element ratio and process conditions to improve the activity and stability of catalysts.

Benefits of technology

Achieve efficient oxygen analysis of reactions (OER) under alkaline conditions, reduce the potential, improve stability, and show excellent catalytic activity in the acidic environment, solving the alternative problem of IRO2.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure CN119370918A_ABST
    Figure CN119370918A_ABST
Patent Text Reader

Abstract

The invention belongs to but not limited to the technical field of OER catalysts, and discloses a method for synthesizing a Co2Mn0. 1Ru0. 9O4 nano-structure and application of the Co2Mn0. 1Ru0. 9O4 nano-structure. The method comprises the steps that a certain amount of MnN2O6. 4H2O, a certain amount of RuCl3 and a certain amount of Co (NO3) 2. 6H2O are dissolved in ethyl alcohol, and ultrasonic treatment is conducted for one hour; transferring the uniformly mixed solution into a water bath, and heating for a period of time until a solid solution is formed; completely drying the solid solution by using a drying oven, and annealing the dried precursor in a tubular furnace in air at 300 DEG C for 4 hours to collect a black product; and washing with water for three times, and washing with ethanol for one time to remove impurities, thereby obtaining the Co2Mn0. 1Ru0. 9O4 nanostructure. The OER catalyst Co2Mn0. 1Ru0. 9O4 provided by the invention has high-performance application of water decomposition under an acidic condition, and a remarkable progress is brought to green energy application.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The present invention belongs to but is not limited to the technical field of OER catalysts, and in particular relates to a method for synthesizing Co2Mn 0.1 Ru 0.9 Methods and applications of O4 nanostructures. Background Art

[0002] Renewable energy sources such as solar and wind energy are considered promising approaches to achieve environmentally friendly and sustainable electricity production. However, both solar and wind energy have intermittent availability. Therefore, large-scale energy storage solutions are needed to bridge the gap between energy supply and demand. Molecular fuels such as oxygen, hydrogen, or hydrocarbons generated by the catalytic oxidation of water or carbon dioxide can serve as alternative energy sources. Precious metals such as platinum (Pt) are considered to be ideal catalysts for the cathode part of water splitting (i.e., water reduction to hydrogen). However, the anode part (which requires the oxidation of water to molecular oxygen under strongly acidic conditions, i.e., the oxygen evolution reaction (OER)) is usually catalyzed by iridium (Ir) or ruthenium (Ru), but finding a catalyst with high activity, good stability, and low cost remains a major challenge. Despite remarkable achievements in non-precious metal catalysts, the biggest problem is that their performance in OER is still insufficient compared to Ru and Ir catalysts. Since OER faces extremely corrosive and aggressive conditions in both alkaline and acidic media, there is still no sufficiently stable and active non-precious metal catalyst. Herein, we report the Co2Mn 0.1 Ru 0.9 O4, which exhibits excellent electrocatalytic OER performance under alkaline conditions with extremely low overpotential (250 mV) and longer stability.

[0003] Water electrolysis can be divided into three main types based on the electrolyte used: alkaline water electrolysis (AWE), solid oxide electrolysis (SOE), and proton exchange membrane (PEM) electrolysis. Among these types, PEM electrolysis stands out in renewable energy storage due to its advantages over AWE, such as lower energy loss, higher efficiency, purer gas, more compact design, higher current density, faster response speed, and less gas crossover. However, PEM electrolysis has a slow oxygen evolution reaction (OER) at the anode, resulting in reduced efficiency, so the development of better OER catalysts is crucial.

[0004] The demand for efficient OER in PEM water electrolysis (PEMWE) has motivated researchers to develop highly active, cost-effective, and durable catalysts. However, common metals are susceptible to corrosion in acidic environments. Therefore, researchers focus on platinum group metals because of their good acid resistance. Studies have shown that factors such as composition and crystallinity have a key impact on OER performance.

[0005] Iridium (Ir)-based and ruthenium (Ru)-based oxides are the best catalysts for the oxygen evolution reaction (OER) under acidic conditions. Although RuO2 has higher catalytic activity, it is less stable than IrO2 due to its greater solubility in acidic environments. The solubility of RuO2 is 30 times that of IrO2, which makes IrO2 more stable and widely used in PEM electrolysis. However, the limited supply of IrO2 restricts its widespread application.

[0006] In view of the above analysis, the technical problem that urgently needs to be solved in the prior art is: an alternative catalyst is needed to replace IrO2 as the anode material in PEM water electrolysis. Summary of the invention

[0007] In view of the problems existing in the prior art, the present invention provides a method for synthesizing Co2Mn 0.1 Ru 0.9 Methods and applications of O4 nanostructures.

[0008] The present invention is achieved by: a synthetic Co2Mn 0.1 Ru 0.9 The method for O4 nanostructures comprises the following steps:

[0009] Step 1, a certain amount of MnN2O6·4H2O, RuCl3 and Co(NO3)2·6H2O were dissolved in ethanol and subjected to ultrasonic treatment for 1 hour;

[0010] Step 2, transferring the uniformly mixed solution into a water bath and heating it for a period of time until a solid solution is formed;

[0011] Step 3, using an oven to completely dry the solid solution, and annealing the dried precursor in air at 300° C. in a tube furnace for 4 hours to collect a black product;

[0012] Step 4: Wash with water three times and then with ethanol once to remove impurities to obtain Co2Mn 0.1 Ru 0.9 O4 nanostructure.

[0013] Furthermore, in the step 1, the amount of MnN2O6·4H2O is 0.0251 g, the amount of RuCl3 is 0.2349 g, the amount of Co(NO3)2·6H1O is 0.498 g, and the amount of ethanol is 10 ml.

[0014] Furthermore, in step 2, the water bath temperature is maintained at 60° C. for 12 hours.

[0015] Furthermore, the drying temperature in step three is 60°C.

[0016] Another object of the present invention is to provide a method for synthesizing Co2Mn0.1 Ru 0.9 Co2MnO4 nanostructures synthesized by a method 0.1 Ru 0.9 Application of O4 nanostructures in water splitting under acidic conditions.

[0017] Another object of the present invention is to provide an OER catalyst, comprising the synthesized Co2Mn 0.1 Ru 0.9 Co2MnO4 nanostructures synthesized by a method 0.1 Ru 0.9 O4 nanostructure.

[0018] In combination with the above technical solutions and the technical problems solved, the advantages and positive effects of the technical solutions to be protected by the present invention are as follows:

[0019] First, a new method was proposed to synthesize Co2Mn 0.1 Ru 0.9 O4 nanostructures designed to enhance oxygen evolution reaction (OER) activity in alkaline water electrolysis. The catalyst showed high efficiency and was able to achieve complete electrocatalytic water splitting. A significant advance in green energy technology has been made by developing an efficient catalyst for water splitting under alkaline conditions. The newly developed Co2Mn 0.1 Ru 0.9 The O4 catalyst exhibited excellent oxygen evolution reaction (OER) activity, and its successful synthesis was confirmed by XRD patterns. The catalyst improved directional electron transport and enhanced overall performance. The synthesis method was simple, using mild conditions, was highly reproducible, and exhibited excellent catalytic activity in an acidic environment. In summary, Co2Mn 0.1 Ru 0.9 O4 nanoparticles have great potential in promoting carbon-free green energy production.

[0020] Second, the technical solution of the present invention provides a method for synthesizing Co2Mn 0.1 Ru 0.9 The method of O4 nanostructure focuses on solving the problems of catalyst activity, insufficient stability and complex process in the prior art, and significantly improves the catalytic performance and industrial applicability. In the existing preparation of nanocatalysts, many processes require high temperature, inert gas protection and multiple complex reaction steps, resulting in high production costs and difficulty in large-scale industrial application. Especially in application scenarios such as environmental protection and energy, traditional catalysts have poor stability and are easily deactivated, resulting in limited service life and economic benefits. The present invention overcomes these technical obstacles by optimizing the element ratio, using ethanol solvent and air annealing.

[0021] First, the present invention enhances the chemical stability of the material by precisely controlling the ratio of Co, Mn and Ru, effectively improving the activity and long-term stability of the catalyst. This element optimization enables the generated nanomaterial to show good durability in practical applications, and is particularly suitable for high-frequency use environments in industry. In addition, the introduction of low-temperature annealing and air oxidation steps in the synthesis process makes the nanostructure more stable, effectively avoiding the problems of lattice defects and material deactivation caused by high-temperature processes.

[0022] Secondly, the present invention uses conventional ethanol solvent and water bath reaction to achieve uniform dispersion of metal precursors under relatively mild conditions, avoiding the complex multi-step processing in traditional processes. Through low-temperature annealing and air oxidation, a nanocatalyst with a high specific surface area and good pore structure is prepared, which greatly improves the adsorption and reaction efficiency of the material. In addition, after a precisely controlled oxidation environment, the Mn element in the material can effectively improve the oxidation activity, thereby enhancing the catalytic effect of the material.

[0023] In addition, this method significantly reduces the reliance on expensive gas protection equipment, making the process simpler and less expensive, and facilitating industrial-scale production. Ultrasonic dissolution at room temperature and subsequent low-temperature treatment make the synthesis process safer and easier to operate, suitable for large-scale continuous production. Combined with the reasonable setting of the annealing temperature, there is no need for complex reaction control and equipment adjustment during the material formation process, meeting the requirements of efficient and simple industrialization.

[0024] In terms of material purity and product consistency, the present invention further removes impurities by multiple water and ethanol washings to ensure high purity and good crystal structure of the final material. 0.1 Ru 0.9 O4 nanostructures exhibit excellent catalytic and adsorption properties, and are suitable for a wide range of fields such as electrocatalysis and environmental purification, meeting the market demand for high-performance catalytic materials.

[0025] Finally, the present invention shows significant advantages in environmental protection and resource utilization. By using oxygen in the air for the oxidation process, the dependence on inert gas is reduced, resource consumption is reduced, and a win-win situation of economic and environmental benefits is achieved. Compared with the traditional high-energy consumption preparation method, the present invention significantly improves energy efficiency and provides technical support for the promotion of nanomaterials in the environmental protection and new energy industries. BRIEF DESCRIPTION OF THE DRAWINGS

[0026] Figure 1 The synthetic Co2Mn provided in the embodiment of the present invention 0.1 Ru 0.9 O4 nanostructure method flow chart;

[0027] Figure 2 The Co2Mn provided in the embodiment of the present invention0.1 Ru 0.9 Schematic diagram of O4;

[0028] Figure 3 is the XRD pattern of the sample provided in the embodiment of the present invention;

[0029] Figure 4 (a) Co2Mn provided in the embodiment of the present invention 0.1 Ru 0.9 SEM images of O4, (b) Co2Mn 0.1 Ru 0.9 EDS images of O4, (c) Co2Mn 0.1 Ru 0.9 Element distribution map of O4, (d) EDS images of Mn, Ru, Co and O;

[0030] Figure 5 The embodiment of the present invention provides Co2Mn in 1M KOH alkaline solution 0.1 Ru 0.9 Comparison of oxygen evolution reaction activity between O4 and Co2MnO4;

[0031] Figure 6 The Co2Mn provided in the embodiment of the present invention 0.1 Ru 0.9 Schematic diagram of the stability of O4. DETAILED DESCRIPTION

[0032] In order to make the purpose, technical solution and advantages of the present invention more clearly understood, the present invention is further described in detail below in conjunction with the embodiments. It should be understood that the specific embodiments described herein are only used to explain the present invention and are not used to limit the present invention.

[0033] like Figure 1 As shown, the embodiment of the present invention provides a method for synthesizing Co2Mn 0.1 Ru 0.9 O4 nanostructure method, comprising:

[0034] 0.0251 g of MnN2O6·4H2O, 0.2349 g of RuCl3, and 0.498 g of Co(NO3)2·6H2O were dissolved in 10 ml of ethanol and subjected to ultrasonic treatment for 1 hour. Next, the mixed solution was transferred to a water bath and the temperature was maintained at 60°C for 12 hours until a solid solution was formed. Then, the solid solution was completely dried in an oven at 60°C. Finally, the dried precursor was annealed in air at 300°C in a tube furnace for 4 hours to collect the black product, which was subsequently washed three times with water and once with ethanol to remove impurities. The synthesis of the reference electrode Co2MnO4 catalyst followed the same procedure.

[0035] Material Characterization:

[0036] The crystal structure (Cu, Kα, 40kV, 25mA) with a scan range of 20° to 80°. The system was equipped with a D\teX Ultra 1D silicon strip detector configured in X-ray fluorescence reduction mode. Powder samples were deposited on a zero-diffraction silicon sample holder for testing. Scanning electron microscopy (SEM) samples were prepared by fixing the powder samples on carbon tape and mounting them on the SEM sample stage. X-ray photoelectron spectroscopy (XPS) was analyzed using a Thermo Fisher ESCALAB 250XI system.

[0037] Electrocatalytic performance:

[0038] 1. Preparation of Catalyst Ink

[0039] To prepare a uniform ink, 5 mg Co2Mn 0.1 Ru 0.9 O4 was dispersed in 1 ml of a mixture consisting of isopropyl alcohol (IPA, 0.48 ml), deionized water (0.48 ml) and 0.04 ml of Nafion solution (1 wt%), followed by 90 min of ultrasonic treatment. 0.1 Ru 0.9 The preparation of O4 catalyst ink followed the same procedure.

[0040] 2. Preparation of Electrodes

[0041] Electrochemical measurements Oxygen evolution reaction (OER) activity and stability tests were performed using an electrochemical workstation (model CHI760D, CH Instruments) and a standard three-electrode electrochemical cell. The catalytic activity of the samples was recorded in 1 M KOH solution, using the prepared samples, platinum sheets and Hg / HgCl as working, counter and reference electrodes. To evaluate the OER activity of the catalysts, linear sweep voltammetry (LSV) was performed in an acidic environment with a voltage range of 0.2 to 1.2 V and a scan rate of 10 mV / s. For the LSV test, the rotation speed of the rotating disk electrode (RDE) was set to 1600 rpm. Electrochemical impedance spectroscopy measurements were performed in a frequency range of 100 kHz to 0.5 Hz with an amplitude of 10 mV when different voltages were applied. Constant current measurement (CP) and cyclic voltammetry (CV) measurements were performed to evaluate the OER stability of the catalysts in acidic electrolytes.

[0042] The following are the Co2Mn 0.1 Ru 0.9Two specific embodiments of the O4 nanostructure synthesis method:

[0043] Example 1: Low temperature synthesis

[0044] 1. Preparation of precursor solution: 0.0251 g of MnN2O6·4H2O, 0.2349 g of RuCl3 and 0.498 g of Co(NO3)2·6H2O were dissolved in 10 ml of ethanol and sonicated at room temperature for 1 h to ensure thorough mixing.

[0045] 2. Solution heating: Transfer the treated solution to a 60°C water bath and react for 12 hours to form a uniform solid solution.

[0046] 3. Drying and annealing: Dry the solid solution in an oven at 60°C, then place the dried precursor in a tube furnace and anneal in an air environment at 300°C for 4 hours.

[0047] 4. Washing and collection: The annealed black powder was washed three times with deionized water and once with ethanol to remove impurities, and finally Co2Mn 0.1 Ru 0.9 O4 nanostructured products.

[0048] Example 2: High temperature optimized synthesis

[0049] 1. Preparation of precursor solution: The same amount of MnN2O6·4H2O, RuCl3 and Co(NO3)2·6H2O were dissolved in 10 mL of ethanol and subjected to ultrasonic treatment for 1 h.

[0050] 2. Solution heating: The ultrasonically treated solution was heated in a water bath at 70° C. for 12 hours to form a solid precursor.

[0051] 3. Drying and annealing: The solid solution was dried in an oven at 70°C, and the dried precursor was annealed in air at 350°C in a tube furnace for 3 hours to further promote the crystallization of the nanostructure.

[0052] 4. Washing and collection: Wash the black powder three times with deionized water and once with ethanol to remove residual impurities and obtain high-purity Co2Mn 0.1 Ru 0.9 O4 nanostructure.

[0053] The above embodiments demonstrate the effects of the process adjustment of the present invention under different temperature conditions and the optimization of the annealing temperature on the formation of the nanostructure and the improvement of the purity.

[0054] Relevant evidence of the technical effects achieved by the embodiments of the present invention.

[0055] XRD ray diffraction analysis

[0056] Figure 3 The XRD pattern of the sample is shown. The X-ray diffraction (XRD) pattern shows that Co2Mn 0.1 Ru 0.9 The diffraction peak of O4.

[0057] Scanning electron microscopy (SEM)

[0058] The surface morphology and microstructure of all samples were observed using a Nova-Nano SEM 450 scanning electron microscope. Figure 4 (a) shows the Co2Mn 0.1 Ru 0.9 SEM image of O4 (best sample). Figure 4 As shown, Co2Mn 0.1 Ru 0.9 The size of the O4 ultrafine nanoparticles is uniformly distributed. The distribution of Co and Mn is also very uniform throughout the RuO2. The elemental composition of the synthesized nanocomposite-based nanomaterials is Figure 4 (b, c, d). Qualitative composition analysis revealed the presence of Mn, Ru, Co, and oxygen elements. The analysis of these elements provides valuable information on the composition and purity of the synthesized nanomaterials.

[0059] Electrochemical measurements:

[0060] All prepared samples were first coated on carbon electrodes and the OER performance was studied using a three-electrode system in 1 M KOH, with Pt and Hg / HgCl as the counter and reference electrodes, respectively. Figure 5 shown. Figure 5 Demonstrated Co2Mn 0.1 Ru 0.9 Linear sweep voltammetry (LSV) curves of O4 and Co2MnO4. 0.1 Ru 0.9 The activity of O4 is 250 mV, and the OER performance of the catalyst is significantly improved compared with the homemade Co2MnO4 without Ru addition. Figure 6 Demonstrated Co2Mn 0.1 Ru 0.9 Stability of O4.

[0061] The above description is only a specific implementation mode of the present invention, but the protection scope of the present invention is not limited thereto. Any modifications, equivalent substitutions and improvements made by any technician familiar with the technical field within the technical scope disclosed by the present invention and within the spirit and principle of the present invention should be covered by the protection scope of the present invention.

Claims

1. A method for synthesizing Co2Mn 0.1 Ru 0.9 O4 nanostructure method, characterized in that, The following steps are involved: Step 1, a certain amount of MnN2O6·4H2O, RuCl3 and Co(NO3)2·6H2O were dissolved in ethanol and subjected to ultrasonic treatment for 1 hour; Step 2, transferring the uniformly mixed solution into a water bath and heating it for a period of time until a solid solution is formed; Step 3, the solid solution is completely dried in an oven, and the dried precursor is annealed in air at 300° C. in a tube furnace for 4 hours to collect a black product; Step 4: Wash with water three times and then with ethanol once to remove impurities to obtain Co2Mn 0.1 Ru 0.9 O4 nanostructure.

2. Synthetic Co2Mn as claimed in claim 1 0.1 Ru 0.9 O4 nanostructure method, characterized in that, In the step 1, the amount of MnN2O6·4H2O is 0.0251 g, the amount of RuCl3 is 0.2349 g, the amount of Co(NO3)2·6H2O is 0.498 g, and the amount of ethanol is 10 ml.

3. Synthetic Co2Mn as claimed in claim 1 0.1 Ru 0.9 O4 nanostructure method, characterized in that, In the step 2, the water bath temperature is maintained at 60° C. for 12 hours.

4. Synthetic Co2Mn as claimed in claim 1 0.1 Ru 0.9 O4 nanostructure method, characterized in that, The drying temperature in step 3 is 60°C.

5. A synthetic Co2Mn according to any one of claims 1 to 4 0.1 Ru 0.9 Co2MnO4 nanostructures synthesized by a method 0.1 Ru 0.9 Application of O4 nanostructures in water splitting under acidic conditions.

6. An OER catalyst comprising the synthesized Co2Mn according to any one of claims 1 to 4 0.1 Ru 0.9 Co2MnO4 nanostructures synthesized by a method 0.1 Ru 0.9 O4 nanostructure.